Neoadjuvant–Adjuvant or Adjuvant-Only Pembrolizumab in Advanced Melanoma - Patel, Sapna P.; Othus, Megan; Chen, Yuanbin; Wright, G. Paul; Yost, Kathleen J.; Hyngstrom, John R.; Hu-Lieskovan, Siwen; Lao, Christopher D.; Fecher, Leslie A.; Truong, Thach-Giao; Eisenstein, Jennifer L.; Chandra, Sunandana; et al. (The New England journal of medicine, 2023)
Patients who received 3 doses of pembrolizumab before surgery and 15 doses after surgery had significantly longer event-free survival than those who received adjuvant-only therapy with 18 doses after surgery.